2014
DOI: 10.1093/neuonc/nou028
|View full text |Cite
|
Sign up to set email alerts
|

Deferred use of bevacizumab for recurrent glioblastoma is not associated with diminished efficacy

Abstract: Deferred use of bevacizumab is not associated with diminished efficacy. Analysis of treatment continuation rates identified patients who may be unable to delay BV therapy. Our findings suggest that there is a fixed survival after BV initiation and that delayed BV treatment is preferable for most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…63 These findings are supported by previous studies, which collectively have reported median overall survival ranges after bevacizumab initiation to be 8.4–9.1 months when used after first recurrence and 7–9.3 months when used after second recurrence. 33,49,63 …”
Section: Bevacizumab Treatment In Glioblastoma: Current Clinical Indisupporting
confidence: 88%
See 2 more Smart Citations
“…63 These findings are supported by previous studies, which collectively have reported median overall survival ranges after bevacizumab initiation to be 8.4–9.1 months when used after first recurrence and 7–9.3 months when used after second recurrence. 33,49,63 …”
Section: Bevacizumab Treatment In Glioblastoma: Current Clinical Indisupporting
confidence: 88%
“…We also know that deferred use of bevacizumab does not diminish efficacy in patients with glioblastoma, indicating that the drug can be considered at any point in the course of disease progression. 63 In a recent study, overall survival and PFS after bevacizumab initiation was similar whether treatment was begun after the first, second, or third recurrence. 63 These findings are supported by previous studies, which collectively have reported median overall survival ranges after bevacizumab initiation to be 8.4–9.1 months when used after first recurrence and 7–9.3 months when used after second recurrence.…”
Section: Bevacizumab Treatment In Glioblastoma: Current Clinical Indimentioning
confidence: 95%
See 1 more Smart Citation
“…However, all patients received standard therapy with radiation treatment and temozolomide, and recent data suggest that bevacizumab (which some patients received), while potentially prolonging progression-free survival by several months, has little impact on survival time. 33 Thus, the overall impact of therapy variability may be limited. Our study was also limited by a small sample size, reducing our ability to detect a potentially significant difference in overall survival (not merely progressionfree survival) between patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study of 100–150 mg/m 2 given weekly on alternate weeks demonstrated a PFS6 of 29% and an ORR of 8%, but reported 56% with grade 3/4 lymphopenia [25]. Although activity was not a primary end point in either study, when compared with bevacizuma, the PFS6 is lower [26]. …”
Section: Discussionmentioning
confidence: 99%